Geographies of commodity chains - Hughes, Alex (Alex Louise); Reimer, Suzanne (Routledge studies in human geography, 2004)
Not only do these case study examples seek to transcend older understandings of production and consumption, but they also explicitly tap into wider public debate about the meanings, origins, and biographies of commodities.